(untitled) (GYMNASIUM, 2008)
The present paper presents a study developed during a 6 months period, on a group of 3 subjects. The purpose of the research was of structuring a kinesitherapeutic intervention program, adapted to the particularities of the subjects and of accomplishing, in the end, a socio-professional reintegration at a top quality level. The group subjects have followed a well structured and organized kinesitherapeutic program (along with medicamentous treatment). Following the research, it has been observed that through the use of a specific kinesitherapeutic conduct at the patients with ankylosing spondylitis, a suspension of the illness’ evolution can be obtained, and also an improvement of the functional parameters, these affirmations being confirmed by the obtained results, objectivised through charts.